2020
DOI: 10.3390/nu12103045
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Fibre from Whole Grains and Their Benefits on Metabolic Health

Abstract: The consumption of whole grain products is often related to beneficial effects on consumer health. Dietary fibre is an important component present in whole grains and is believed to be (at least partially) responsible for these health benefits. The dietary fibre composition of whole grains is very distinct over different grains. Whole grains of cereals and pseudo-cereals are rich in both soluble and insoluble functional dietary fibre that can be largely classified as e.g., cellulose, arabinoxylan, β-glucan, xy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
57
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(85 citation statements)
references
References 150 publications
(196 reference statements)
3
57
0
1
Order By: Relevance
“…However, the reported values are very inconsistent; so that 0.4–0.9% (Demirbas, 2005 ), <0.06% (Burton and Fincher, 2012 ), and up to 20% (Fincher and Stone, 2004 ) were reported in rice endosperm. The MLG content was reported to account for 20% of the total dietary fiber content in wheat (Prasadi and Joye, 2020 ). Wirkijowska et al ( 2012 ) reported that the content of (1–3) (1–4)-β- d -glucans in barley kernel ranged between 4.04 and 5.71% of dry matter, and Garcia-Gimenez et al ( 2019 ) expressed that barley has a considerably higher MLG content (4–10%) compared with wheat (1%) or rice (<0.06%), although (Fincher, 2009a ) reported that (1–3) (1–4)-β- d -glucans constitute up to 70% of starchy endosperm in barley.…”
Section: Discussionmentioning
confidence: 99%
“…However, the reported values are very inconsistent; so that 0.4–0.9% (Demirbas, 2005 ), <0.06% (Burton and Fincher, 2012 ), and up to 20% (Fincher and Stone, 2004 ) were reported in rice endosperm. The MLG content was reported to account for 20% of the total dietary fiber content in wheat (Prasadi and Joye, 2020 ). Wirkijowska et al ( 2012 ) reported that the content of (1–3) (1–4)-β- d -glucans in barley kernel ranged between 4.04 and 5.71% of dry matter, and Garcia-Gimenez et al ( 2019 ) expressed that barley has a considerably higher MLG content (4–10%) compared with wheat (1%) or rice (<0.06%), although (Fincher, 2009a ) reported that (1–3) (1–4)-β- d -glucans constitute up to 70% of starchy endosperm in barley.…”
Section: Discussionmentioning
confidence: 99%
“…As a result of the varied nutritional content and bioactive compounds in the food items, different physiological effects may be expected (36,37) . Antidiabetic properties, decreased inflammation, and the modulation of lipid metabolism and oxidative stress have been documented in in vitro studies and clinical trials investigating health benefits of consuming brown rice (38) .…”
Section: Discussionmentioning
confidence: 99%
“…AX from wheat and βG from barley and oat are mostly soluble, whereas AX from maize is mainly insoluble ( Knudsen, 2014 ). Solubility impacts their physiological properties with soluble DF (SDF) playing the most of healthy functions ( Prasadi and Joye, 2020 ).…”
Section: Dfs In Cereal Grainmentioning
confidence: 99%
“…Among major cereals, wheat grains contain 12% of DF, followed by maize (7.3%) and brown rice (3.4%); barley ( Hordeum vulgare ) has the highest content in DF (17%) ( Prasadi and Joye, 2020 ). Minor cereals, such as oat and rye, contains 10.5 and up to 20% of total DF.…”
Section: Introductionmentioning
confidence: 99%